The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1038/ng1197-277
|View full text |Cite
|
Sign up to set email alerts
|

Communal discourse as a supplement to informed consent for genetic research

Abstract: Genetic technologies present unique problems for the practice of informed consent. They provide information that may affect a study participant's family or kindred, which may be identifiable as an ethnic or locally isolated population. That information may be used to construct adverse perceptions of such identifiable populations, including non-participants who may not have been informed of or consented to the analyses. To address collective implications of genetic research, we describe a process that can suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…However, the definition of the ''public'' is subject to dispute and the nature of their involvement is unclear. The need to inform, include and obtain the consent of the community or the population is put forward without specifying the character of this involvement [69][70][71]. Finally, the process of building trust is central to all kinds of biobank projects, whether they rely on patient or on general population studies.…”
Section: Public Engagement and Trustmentioning
confidence: 99%
“…However, the definition of the ''public'' is subject to dispute and the nature of their involvement is unclear. The need to inform, include and obtain the consent of the community or the population is put forward without specifying the character of this involvement [69][70][71]. Finally, the process of building trust is central to all kinds of biobank projects, whether they rely on patient or on general population studies.…”
Section: Public Engagement and Trustmentioning
confidence: 99%
“…39,40 Some have suggested that the social group itself should be involved in the process of research. 41,42 This is the process which was undertaken in Iceland when Decode Genetics 43 proposed to create an electronic database of the country's health records that could be linked to individuals genotype. 44,45 Part of the purpose of our study was to provide an example of the process of assessing the attitudes of a community before pursuing population-based genetic research.…”
Section: Tablementioning
confidence: 99%
“…The analysis we propose focuses on genetic research with American Indian and Alaska Native communities, as several participatory models have been tried in these contexts (18 …”
mentioning
confidence: 99%